Comparison of mammographic breast density of women from China with women from Australia using percentage density: a comparative study. Issue 1 (October 2019) - Li, Tong; Li, Jing; Ren, Jiansong; Heard, Rob; Gandomkar, Ziba; Dai, Min; Brennan, Patrick
Abstract: Background: Mammographic breast density (MBD) has been reported to be one of the strongest risk factors of breast cancer in western countries. However, the MBD profile in China is unclear. We aimed to compare the MBD of women in China with the MBD of women in Australia using percentage density. Methods: This study included 3250 Chinese women (Han origin only) aged 45–69 years who participated in the Cancer Screening Program in Urban China (CSPUC) and 1384 age-matched Australian women (including women with background of Australian, New Zealander, British, Irish, European, and American) from the Lifepool project. Mammograms for each woman were collected and data on women's age, height, weight, level of education, age at menarche, breastfeeding history, breastfeeding duration, menopause status, and age at menopause were obtained. We assessed MBD using an automatic algorithm AutoDensity that produces MBD percentage values. We used a Student's t-test to compare the mean MBDs between Chinese and Australian women, for all women, pre-menopausal women, and post-menopausal women groups. Two-way ANOVA was performed to examine if there was an interaction between country and each of the above factors on MBD. This study was approved by the Human Research Ethics Committee of the University of Sydney (Project number: 2014/768) and Institutional Review Board of Cancer Institute and Hospital, Chinese Academy of Medical Sciences (Project number 15-062/989), and consent form was obtained from each participant through CSPUC and Lifepool programmes. Findings: Chinese women had 9·61% (95% CI 8·84–10·37), 8·20% (6·60–9·79) and 9·28% (8·42–10·15) higher MBD than did their Australian counterparts in all, pre-menopausal, and post-menopausal women, respectively (all p<0·0001). The MBD in Chinese women was higher than that in Australian women in each age group (45–49 years, p<0·0001; 50–54 years, p<0·0001; 55–59 years, p<0·0001; 60–64 years, p<0·0001; 65–69 years, p=0·0003) and each body-mass index (BMI) category (<18·50 kg/m 2, p=0·0208; 18·50–24·99 kg/m 2, p<0·0001; ≥25·00 kg/m 2, p<0·0001). There were significant interactions between country (China or Australia) and age groups (F(4, 4624)=4·12, p=0·0025), BMI classifications (F(2, 4628)=3·92, p=0·0198), breastfeeding history (F(1, 4479)=17·79, p<0·0001), and duration of breastfeeding (F(1, 3526)=66·90, p<0·0001). Interaction was not found for education (F(2, 4628)=0·14, p=0·8666), age at menarche (F(1, 4630)=0·72, p=0·3979), menopause status (F(1, 4605)=1·45, p=0·2293), and age at menopause (F(1, 3172)=3·04, p=0·0812). Interpretation: This study compared MBD between Chinese and Australian women and significant differences were found between the two populations. Our reported discrepancies around percentage density between two populations and the different effects on MBD from demographic and reproductive factors provide a better understanding of the optimal breast cancer screening approaches in China and challenge the one-size-fit-all strategy. Funding: None.